LESSON STUDY PADA PERKULIAHAN MICROTEACHING - Hera Deswita (Pendidikan Matematika | STKIP YM Bangko, 2019)
Teacher competency improvement in teaching mathematics can be done through the implementation of lesson studies in microteaching lectures. The lesson study is carried out collaboratively and continuously. The purpose of lesson study for teacher improvement activities in conducting the learning process in class. The stages of lesson study activities are plan, do, and see. The purpose of this study is to describe the implementation of lesson study in microteaching lectures. Based on observations, interviews and documentation that have been done, it can be concluded that the implementation of lesson studies in microteaching lectures can improve student skills in designing, implementing and evaluating learning